Terror and Resilience: One Day in the Life of Aleksandr Solzhenitsyn - Miguel Angel Belmonte (Ignatianum University Press, 2018)
During 2017 numerous events related to the centenary of the Russian Revolution took place. December 2018 also marks the 100th anniversary of the birth of one of the most relevant figures in the understanding of totalitarianism: Aleksandr Solzhenitsyn. Between these two centenaries, this article provides a contribution to the understanding of the way in which the narrative, based on a biographical and autobiographical background, of Solzhenitsyn's works allows the phenomenon of Terror to be faced.